Ultrasound of local complications in hand surgery: a pictorial essay - Bianchi, Stefano (J Ultrasound, 2020)
Early detection of local complications (venipuncture complications, nerve lesions, infections, arthritis, and tenosynovitis, tendon adhesions and re-tears, complications related to orthopaedic hardware) after hand surgery is required for prompt treatment. Ultrasound has proven to be a valuable imaging modality for detecting and assessing a variety of disorders of the wrist and hand. The purpose of this pictorial essay is to present a wide range of complications after wrist and hand surgery assessed by ultrasound.